Gone with the flow - Assessment of personal care products in Portuguese rivers. (April 2022) - Homem, Vera; Llompart, Maria; Vila, Marlene; Ribeiro, Ana R.L.; Garcia-Jares, Carmen; Ratola, Nuno; Celeiro, Maria
Abstract: Although there are several works in the literature that study the presence of pharmaceuticals and personal care products (PPCPs) in surface waters, the vast majority focus their attention on pharmaceuticals and little information is found about personal care products (PCPs). Therefore, this study focused, for the first time, on the monitoring of five classes of PCPs – fragrance allergens, synthetic musks, phthalates, antioxidants, and ultraviolet-filters - in the surface water of four small-size typically pollution-impacted Portuguese rivers (Ave, Leça, Antuã and Cértima). A solid-phase microextraction (SPME) followed by gas chromatography - tandem mass spectrometry (GC-MS/MS) protocol was employed to analyse surface water samples collected in two seasonal campaigns - summer and winter (34 samples per season). A total of 22 out of 37 target PCPs were detected concomitantly at least once in one sampling point, being the most frequently detected α-isomethyl ionone, galaxolide, tonalide and cashmeran. The highest concentrations were confirmed for diethylhexyl phthalate (610.6 ng L −1 ), galaxolide (379.2 ng L −1 ), geraniol (290.9 ng L −1 ), linalool (271.2 ng L −1 ), benzophenone-3 (254.1 ng L −1 ) and citronellol (200.2 ng L −1 ). Leça River, traversing the more densely urban and industrialized area, had the highest levels of contaminants, which were also found in the sampling points located downstream of wastewater treatment plants discharge points. In general, higher levels were detected in summer, when the river flows are lower. Hazard quotients were determined and octocrylene, tonalide, and geraniol presented values above 1 in some sampling sites, which may indicate an ecotoxicological risk to the aquatic environment. The results presented suggest that these three PCPs should be included as priority pollutants in environmental monitoring schemes in surface waters, due to their high detection, persistence, and potential adverse effects. Graphical abstract: Image 1 Highlights: Thirty personal care products were detected in water from four Portuguese Rivers. α-isomethyl ionone, galaxolide, tonalide, cashmeran were the most frequently detected. The highest concentrations were found for diethylhexyl phthalate and galaxolide in the water. Urban and industrialized sites had the highest contaminant levels, particularly in summer. Octocrylene, tonalide, and geraniol may pose risk to the aquatic life.